170k views
2 votes
Consider the given function.

Consider the given function.-example-1
User Ryan Gates
by
4.6k points

1 Answer

3 votes

Answer:

To determine the inverse of the given function, change f(x) to y, swich x and y, and solve for y.


f^(-1) (x) = (ln(x+4))/(2)

Explanation:

To determine the inverse of the given function, change f(x) to y, swich x and y, and solve for y.

Oiriginal function:
f(x) = e^(2x) -4

Change f(x) to y:
y = e^(2x) -4

Switch x and y:
x = e^(2y) -4

Solve for y:


x = e^(2y) -4


x+4= e^(2y)


ln(x+4)= 2y


y = (ln(x+4))/(2)

Then:
f^(-1) (x) = (ln(x+4))/(2)

User Matt Sheppard
by
5.0k points